Effects of pilot-plant photochemical pre-treatment (UV/H2O2) on the biodegradability of aqueous linear alkylbenzene sulfonate (LAS) - Mehrab Mehrvar; Gelareh Bankian Tabrizi; Nabil Abdel-Jabbar (International Journal of Photoenergy)
The effects of the photochemical pre-treatment by using a pilot-plant UV/H2O2 process on the biodegradability of aqueous linear alkylbenzene sulfonate (LAS) were studied. It was observed that the photochemical pre-treatment of the LAS solutions by UV-254/H2O2 increased the biodegradability of LAS solutions. Aqueous solutions with higher concentrations of LAS (> 100 mg/L) were non-biodegradable. The ratio of BOD5/COD of the pre-treated LAS solutions was increased, indicating that the pre-treated LAS solutions were more biodegradable. This ratio was improved as the LAS solutions were more pre-treated. Also, the biodegradability factor for the pre-treated LAS solutions was increased as the time of the photochemical pre-treatment was increased.